STUDY ON THE QUALITY OF FOOD AND BEVERAGE PRODUCTS IN SUKAJADI VILLAGE, BOGOR - Sekti Rahardjo; Dina M. Soeswoyo; Maidar Simanihuruk; Yuviani Kusumawardhani (Jurnal Cakrawala Ilmiah, 2022)
Tourism is an industry in which there are components called 4As: attractions, accessibility, amenities, and ancillary services. Of the four components, quite a lot of expenditure is made by tourists on amenities related to the purchase of food and beverages. Village development is carried out by utilizing the various potentials in it in order to improve the village economy. One of the villages with potential that can be optimized is Sukajadi Village, located in Tamansari District, Bogor Regency. Sukajadi Village has provided various food and beverage products to attract tourists, including the CheesePal and Mipala Sukajadi which are local products made from nutmeg developed by the Bogor Tourism College. The purpose of this study is to increase public knowledge about the quality of food and beverage products in Sukajadi Village, to provide maximum value and benefits for consumers regarding the quality of food and beverage products. This research was conducted through data collection techniques by distributing questionnaires to 100 respondents, direct observation and literature study. Based on the calculation of the aspects of Color, Portion, Temperature and Texture on the food and beverages provided in Sukajadi Village, a Mean value of 3.5 was obtained, while the Taste, Appearance, Shape and Aroma aspects obtained a Mean value of 3.6. These two values indicate that on average the respondents quite agree with the good quality of food and beverage products provided in Sukajadi Village. The food and drinks provided are quite acceptable.